Efisiensi Penggunaan Modal Kerja pada Agen BRILink dalam Menghadapi Tantangan Ekonomi: Studi Kasus Agen BRILink - Jamroh Jamroh; enik rahayu (Mahesa Research Center, 2026)
This article aims to analyze the efficiency of working capital utilization at BRILink Agent Arnawama Klepu in facing dynamic economic challenges. The problem focuses on how working capital management is implemented to maintain liquidity, ensure operational continuity, and support business sustainability amid fluctuations in service demand and changing economic conditions within the community. To address this issue, the study employs theoretical frameworks of working capital management, liquidity theory, and operational efficiency in the context of micro financial service enterprises. Data were collected through in-depth interviews with the agent manager and related parties, direct observation of daily operational activities, and supporting documentation, and were analyzed qualitatively using an interactive analysis model. The findings indicate that working capital management at BRILink Agent Arnawama Klepu has been relatively efficient in supporting daily transaction activities and maintaining sufficient cash availability to meet customer needs. However, the achieved efficiency remains operational in nature and has not yet been fully supported by systematic financial planning and structured financial record-keeping. This study concludes that strengthening working capital management through more structured cash planning and orderly financial recording is a strategic step to enhance efficiency, maintain business stability, and improve the adaptability of BRILink Agents in responding to future economic challenges.